UP diksiyonaryong Filipino - Almario, Virgilio S. 1944-.; University of the Philippines (Diliman). Sentro ng Wikang Filipino (Quezon City Sentro ng Wikang Filipino, Unibersidad ng Pilipinas, 2001)
Headed by Virgilio S. Almario with the whole U.P. Sentro ng Wikang Filipino resources, this dictionary that includes new emerging terms in the field of science and technology, mathematics, philosophy, social studies and arts and literature, came to reality. It contains more than 100,000 entries that summarize the different languages in the Philippines.
Jointly published with Anvil Publication.
Keywords: Filipino language -- Dictionaries